Incentivizing Vegetable Consumption in School‐Aged Children: Evidence from a Field Experiment. Issue 1 (21st July 2019) - De Marchi, Elisa; Cavaliere, Alessia; Nayga, Rodolfo M.; Banterle, Alessandro
Abstract : We conducted a field experiment to test the effect of nonmonetary incentives in increasing children's vegetable consumption during lunch at school. We measured children's daily vegetable consumption for four consecutive weeks prior to the provision of incentives, for four consecutive weeks during the incentive provision, and for three consecutive weeks right after the provision of incentives. To check the longer‐term effect of the incentive provision, we measured children's daily vegetable consumption 11 weeks after the postintervention period. Results suggest that the incentives are effective in increasing vegetable consumption and that this effect persisted several weeks after the provision of the incentives ended. This is an important topic since gaining a better understanding of effects of nonmonetary incentives can help in the design of nutrition and health policies aimed at improving the dietary behavior of children and potentially reducing childhood obesity.